Effect of freezing on the quality of breast meat from broilers affected by wooden breast myopathy - Villegas-Cayllahua, Erick Alonso [UNESP]; de Mello, Juliana Lolli Malagoli [UNESP]; Dutra, Daniel Rodrigues [UNESP]; de Oliveira, Rodrigo Fortunato; Cavalcanti, ÉrikaNayara Freire [UNESP]; Pereira, Mateus Roberto [UNESP]; Ferrari, Fábio Borba [UNESP]; de Souza, Rodrigo Alves [UNESP]; Carneiro, Nívea Maria Gomes Misson [UNESP]; Fidelis, Heloísa de Almeida [UNESP]; Giampietro-Ganeco, Aline [UNESP]; de Souza, Pedro Alves [UNESP]; et al. (Elsevier, 2023)
The objective of the present study was to characterize possible variations in the quality of wooden chicken breast meat during freezing for 12 mo, in order to prove whether the shelf life recommended by the industry allows the storage of that type of meat without compromising its consumption. Three hundred samples of male Cobb 500 broilers slaughtered at 42 d of age were used. Part of the samples (n = 20 normal—control group; n = 20 moderate degree; n = 20 severe degree) were analyzed on the day of collection (beginning), previously kept under refrigeration (4°C). The other samples were stored (−18°C) for up to 12 mo. At the end of each proposed freezing period (3, 6, 9, and 12 mo), physical and chemical analyses were performed (per period: n = 20 normal—control group; n = 20 moderate degree; n = 20 severe degree). Color (L*, a*, and b*), pH, water-holding capacity, cooking losses, tenderness, lipid oxidation, chemical composition, cholesterol concentration, mineral profile, and collagen concentration were evaluated. The physicochemical quality of wooden chicken breast meat is significantly altered during frozen storage for 12 mo, being of inferior quality when compared to normal chicken breast meat, which can negatively affect consumer acceptance. However, it should be noted that even after 12 mo of freezing, the meats did not show oxidative rancidity.
Keywords: condition; emerging myopathy; meat quality; storage; tenderness